Effects of Clove Leaf Essential Oil (Syzygium aromaticum) in Inhibiting Biofilm Formation on Candida albicans Isolate - Rifai, Achmad; Endraswari, Pepy Dwi; Setiawati, Yuani; Koendhori, Eko Budi (Universitas Airlangga, 2024)
Highlights: Candida albicans is capable of forming biofilm, which can lead to resistance to antifungal treatments. Clove leaf essential oil, which can inhibit biofilm formation, making it a potential anti-biofilm agent. Abstract Introduction: Candida albicans (C. albicans) has a virulence factor, like biofilm formation. Biofilm is a three-dimensional structure that plays a role in antimicrobial resistance, thus requiring antibiofilm agents to address this problem. One of them is Clove leaf (S. aromaticum). S. aromaticum has active phytochemicals (eugenol, β-caryophyllene, and others) that can inhibit biofilm formation in microorganisms, including fungi. This study aimed to prove the effect and to find a concentration of Clove leaf essential oil that affects the biofilm formation of C. albicans isolate. Methods: This study used a microtiter plate with a two-fold dilution technique. The tested concentrations were 6.25%, 3.125%, and 1.5625%. The positive control was 200 µL of C. albicans biofilm suspension, and the negative control was 200 µL of tryptic soy broth media, and all were repeated four times. The biofilm was observed using crystal violet and evaluated using optical density. The data was analyzed statistically using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26, with a p<0.05 considered statistically significant. Results: The Optical density (O.D.) of the isolate was 2.039, while the negative control was 0.349, indicating that the isolate was a strong biofilm former. The concentrations of 6.25%, 3.125%, and 1.5625% showed inhibition percentages of 8.533%, 17.214%, and 8.484%, respectively. The Optical density was found to be normally distributed but not homogeneous p>0.05, The Kruskal-Wallis’s test was significant, and the Mann-Whitney test was not significant between test groups and positive control. Conclusion: Clove leaf essential oil has inhibitory effects on C. albicans biofilm isolates. However, statistically, there was no significant difference between the test groups and the positive control.